ANALISIS PEMANFAATAN LIMBAH LIDI KELAPA SAWIT UNTUK PENINGKATAN PENDAPATAN PETANI LIDI KELAPA SAWIT DI KECAMATAN TUALANG - , Eriyati, Alsa Indra Jati Hartono ,H. Hendro Ekwarso (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The purpose of this study was to determine the amount of income of oil palm stick farmers who collect oil palm sticks and farmers who process oil palm sticks as crafts in Tualang District. The sampling method used in this study is the Solvin (Sample) technique. Data analysis used in this research is descriptive quantitative data and different test and average difference test (Independent Sample T-test) with SPSS assistance. The results of this study indicate that there are benefits for oil palm stick farmers in the form of increased income from the results of the sticks and there is a difference in income between farmers who collect oil palm sticks and farmers who process oil palm sticks as crafts, where the income of stick farmers who collect is lower than farmers who process oil palm sticks as a craft are increasing. Keywords:From palm oil stick waste, Income, Stick Farmer